The Effect of Trade Openness on Inflation in D-8 Member Countries with an Emphasis on Romer Theory - Sepehrivand, Aram; Azizi, Jabar (Asian Journal of Economic Modelling, 2016)
Economists believe that globalization increases the role of external factors and reduces the role of internal factors in the process of inflation. Despite the rising global oil prices during recent years and the adoption of expansionary monetary policies in most countries, global prices have had a low and stable level growth. The adoption of expansionary monetary policies in D-8 member countries has been conducive to prices growth and inflation. Economists believe this phenomenon is caused by many reasons and have tried to analyse the effect of globalization on countries inflation. Openness as an indicator of globalization can affect the rate of inflation. The present study aims to investigate the effect of trade openness on D-8 Member countries with an emphasis on Romer theory. The Econometric method used in this research is the method of regression using panel data. The results show that trade openness has a positive and significant effect on the inflation as the dependent variable. This result does not confirm the Romer theory and shows that the influence of monetary policies on the international markets is very high and the degree of influence leads to swings in consumption demands for domestic goods. According to new theories of growth, trade openness reduces inflation rates by increasing production efficiency, better allocation of resources, better use of capacities and increasing foreign investments to reduce the inflation rate. In this regard, lack of full competition in domestic markets and price instabilities in non-commercial sectors has led to a reverse relationship between inflation and trade openness.